Dehydrogenase Activities of Flooded Soils: A Review (Aktivitas Dehidrogenase pada Tanah Sawah: Review) - Mambu, Susan Marlein (JURNAL BIOS LOGOS, 2014)
Abstract The definition of soil quality encompasses physical, chemical and biological characteristics, and it is related to fertility and soil health. Soil enzyme activities are the direct expression of the soil community to metabolic requirements and available nutrients, can be used as soil quality indicators. Among all enzymes in the soil environment, dehydrogenases are one of the most important, and are used as indicator of overall soil microbial activity. Flooded soils present a unique situation since they are predominantly under anaerobic conditions in several physical, chemical, and biological characteristics. Flooding changes the chemistry, microbiological properties, and nutrient supply capacity of soil. In particular, the effect of flooding causes an increase on soil dehydrogenase activity. This review examines selected papers containing soil dehydrogenase activities in flooded soil that could be used to determined effect of flooding on soil dehydrogenase activity. Keywords: dehydrogenase activities, flooded soils, soil quality Abstrak Definisi kualitas tanah meliputi faktor fisik, kimia dan biologi, dan terkait dengan kesuburan dan kesehatan tanah. Aktivitas enzim tanah adalah ekspresi langsung dari komunitas tanah untuk melakukan proses metabolik untuk menghasilkan nutrisi, dan dapat digunakan sebagai indikator kualitas tanah. Di antara semua enzim dalam lingkungan tanah, dehydrogenase adalah salah satu yang paling penting, dan digunakan sebagai indikator aktivitas mikroba tanah secara keseluruhan. Tanah sawah dengan kondisi tergenang menyajikan situasi yang unik karena secara fisik, kimia, dan biologi berada dalam kondisi anaerob. Penggenangan menyebabkan terjadinya perubahan secara kimia, mikrobiologi, dan kapasitas pasokan hara tanah. Secara khusus, Efek penggenangan menyebabkan peningkatan aktivitas dehidrogenase tanah. Tulisan ini mengkaji beberapa penelitian mengenai aktivitas dehidrogenase pada tanah sawah, yang dapat digunakan untuk menentukan efek pengenangan terhadap aktivitas dehidrogenase tanah. Kata Kunci: aktivitas dehidrogenase, tanah sawah, kualitas tanah